MALEIN AGIDIRID, MONOETANOLAMIN VA FOSFAT KISLOTA MMF-2 MARKALI KOMPOZIT KORROZIYA INGIBITORINING SINTEZI ("Conference on Universal Science Research 2023", 2024)
This article studies the synthesis of corrosion inhibitor based on maleic anhydride, monoethanolamine and phosphoric acid. The composition of the obtained corrosion inhibitor was analyzed using IR spectra